Prospects, Challenges, and Strategies of Business Development Center in Generating University Income - Azizah, Siti; Romaisyah, Luqita (Jurnal Mebis, 2025)
This study aims to explore the prospects, challenges, and strategies of the Business Development Centre (PUSBIS) of UIN Sunan Ampel Surabaya in generating University revenue in order to become a State University with Legal Entity (PTNBH). The analysis of prospects and challenges is compiled based on four Balanced Scorecard (BSC) perspectives mapped into a SWOT analysis. Furthermore, the results of the analysis are used to formulate appropriate strategies. The research method applied is qualitative, using in-depth interview techniques, observation, and document analysis to collect data. The results of the study indicate that PUSBIS has opportunities in optimising asset utilisation, strategic partnerships, and digitalising business processes. On the other hand, PUSBIS also faces various challenges, such as financial management regulations, limited resources, and market competition. The recommended strategies include optimising asset utilisation, budget reformulation, improving service quality, as well as monitoring and evaluating customers, strengthening distinction as an Islamic-based University, digitalising business processes, developing strategic partnerships, product and service innovation, and sustainable human resource development.